“DMAIC 기반 배터리 생산시스템 과제해결방법론”의 효율성 및 적합성 평가: 개선을 위한 적용 가능성 연구 - 박신철; 이주연 (시스템엔지니어링학술지, 2024)
The DMAIC methodology, which is most familiar to battery production system developers, is partially inadequate in its conformity to utilize battery production system tasks, so it is necessary to improve the function and structure of the methodology, but many battery production system developers use the DMAIC method based on experience, causing side effects such as confusion, delay in tasks, and insufficient performance during tasks. Accordingly, we intend to conduct an empirical study to improve the "efficiency improvement and conformity evaluation method" so that the DMAIC methodology can be used more reasonably and easily. Using the three-stage research model, we derive components that affect conformity through literature and questionnaire surveys in the first stage, use relational characteristics between components in the second stage to confirm the effect on conformity, and use the relational characteristics in the third stage to confirm the possibility of improving efficiency by applying them to the DMAIC methodology in actual cases. Finally, the "Conformity Assessment Index (CAI) equation" based on relational characteristics is established to enable effective conformity evaluation and continuous improvement.
Keywords: DMAIC; problem solving method; system developer; battery production system; components; a conformity assessment index